(untitled) (Al-Academy, 2023)
The article analyzes the role of material not only as a technical medium for creating image but also as an autonomous semantically meaningful system of expression that provides the image with substance and shapes the identity of the artwork. We investigate how material became a central element of artistic expression, bridging the gap between visual image and sensory experience. The study traces the development of material in visual art, from the dominance of representational forms throughout much of art history to contemporary abstraction, which redefined the artwork beyond traditional image. It highlights significant transformations in the use of material, particularly with movements such as collage and art brut, where material emerged as a decisive factor in creating visual and emotional impact. These shifts emphasize how material evolved into a core component of modern and contemporary art, shaping interactions between artworks and their audiences. On a philosophical level, the study applies phenomenological theory to analyze how an artwork transcends its physical properties, engaging viewers in perceptual and cognitive experiences. We also consider the role of abstract elements like color, texture, and depth in redefining the artwork as an independent entity. This leads us to ask ourselves: can material be separated from image, or is it the foundation from which artistic meaning emerges and continues to evolve?